Discursive ideologies: reading western rhetoric - Knoblauch, C. H., author; Utah State University Press, publisher (Colorado State University. Libraries, 2014)
In Discursive Ideologies, C.H. Knoblauch argues that European rhetorical theory comprises several distinct and fundamentally opposed traditions of discourse. Writing accessibly for the upper division student, Knoblauch resists the conventional narrative of a unified Western rhetorical tradition. He identifies deep ideological and epistemological differences that exist among strands of Western thought and that are based in divergent "grounds of meaningfulness." These conflicts underlie and influence current discourse about vital public issues.
The Meaning of Meaning -- Magical Rhetoric -- Ontological Rhetoric -- Objectivist Rhetoric -- Expressivist Rhetoric -- Sociological Rhetoric -- Deconstructive Rhetoric -- Afterword: Critical Reflections.
Keywords: Rhetoric -- Political aspects; Rhetoric -- Philosophy